The Grammatical Performativity of Exclamatory Such in Declaratives: A Corpus Based Study - Hessan, Tayseer Flaiyih (International Journal of Psychosocial Rehabilitation, 2020)
This study has theoretical and practical sides. Theoretically, it investigates the grammatical performativity of exclamatory such. That is, its significance as a grammatical means in achieving the exclamative illocution or force in declaratives. Practically, this study focuses on the grammatical surroundings in which exclamatory such occurs, i.e., the kinds of nouns it co-occurs with. The aim of this study is to elaborate on the role which the word such plays in declaratives to perform the illocution or force of exclamation, an illocution or force different from the typical one usually associated with decalartives. The procedures followed here is: theoretically surveying the word such in English syntax focusing on its exclamative identity in declaratives, providing a description of the semantics of exclamation where the researcher tries to give special draw on exclamatory such, giving a pragmatic account on exclamation as a speech act with an attempt to focus on exclamatory such, choosing a corpus from the BNC and Webcorp searching engines, depending on a concordancing or co-occurring program as searching tool to discover the kind of environment exclamatory such is expected to be found in. The study concludes that the exclamatory such can be a rare word at least in the chosen corpora. Basing on the chosen corpora, another conclusion is that the kind of nouns exclamatory such tends to mostly co-occur with is the singular countable noun.